Achievement emotions among adolescents receiving special education support in mathematics - Marja Eliisa Holm; Piia Maria Björn; Anu Laine; Johan Korhonen; Markku Sakari Hannula (Elsevier, 2022)
This study investigated mathematics-related achievement emotions among Finnish adolescents (N = 1379) receiving special education support (SEdS) in self-contained and general mathematics classrooms and receiving no mathematics SEdS through multilevel modeling. Mathematics performance, gender, and classroom size were controlled for. Adolescents receiving SEdS in general classrooms reported less enjoyment and pride and more anger, anxiety, shame, hopelessness, and boredom than those receiving SEdS in self-contained classrooms and those receiving no SEdS. In contrast, adolescents receiving SEdS in self-contained classrooms reported more enjoyment and pride and less anger, anxiety, and hopelessness than those receiving no SEdS. Furthermore, adolescents receiving no SEdS reported more anxiety, hopelessness, and boredom in general classrooms when the proportion of classmates receiving SEdS was higher. We discuss the practical implications for developing SEdS in relation to achievement emotions.